Minat Beli Ditinjau dari Pemasaran Online, Kualitas Pelayanan, dan Tingkat Kepercayaan Kue Lumpur Bakar Shekinah Boyolali - Putri, Restiani Siwi; Sarsono; Raisa Aribatul Hamidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of marketing online service quality, as well as the level of trust in consumer buying interest. This research method uses a quantitative descriptive approach. The population in this study is consumers of Kabar Shekinah Mud Cake Shop in 2023-2024, the number of which is not known with certainty. The sampling technique in this research uses techniques purposive sampel with a sample of 100 respondents. Data collection using a scale questionnaire linkert to measure respondents' answers. The data analysis technique used is statistical analysis with multiple linear regression, F test, t test, and coefficient of determination. Data analysis was assisted by SPSS version 25 software. The results of this research show that partially online marketing and service quality has a positive and significant effect on purchasing interest at the Bakar Mud Cake Shop Shekinah Boyolali. Meanwhile, the level of trust has an insignificant positive effect on purchasing interest at the Bakar Mud Cake Shop Shekinah Boyolali. Purchase interest can be explained by marketing variables online, service quality, and trust level of 64%